Peningkatan Penguasaan Kosakata Melalui Teknik Permainan Teka-teki Silang di Kelas VII.A SMPN 2 Sungai Penuh - Elviza, Yulia; Emidar, Emidar; Noveria, Ena (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2013)
The purpose of this article is to describe the process and result the improvement of vocabulary mastery at grade VII A of Junior High School 2 Sungai Penuh through Crossword Game Technique. The Increase vocabulary mastery of the students seen by the mastery of synonyms, antonyms, and the meaning of the term as the indicator. The findings of the study was the technique of crossword puzzles game can increase students vocabulary, it seen from the average of pre-cycle 53.92%, first cycle 69.50% and second cycle 75.25%. It can be concluded that the vocabulary mastery of the students increased significantly with an average increase from cycle I to cycle II 5, 75% with the students completed amount to 36 students (90%) of the total.